ผลของการจัดกิจกรรมการเรียนรู้คณิตศาสตร์โดยใช้รูปแบบการร่วมมือแบบสืบสอบที่มีต่อความสามารถในการให้เหตุผลและการสื่อสารทางคณิตศาสตร์ของนักเรียนมัธยมศึกษาปีที่ 2 - เสมา ปภัสชญา; ทำสวน จงกล (An Online Journal of Education, 2018)
The purposes of this study were to 1) compare mathematical reasoning and communication abilities of students learning by using an organizing mathematics learning activities using inquiry co-operation model between before and after learning, 2) compare mathematical reasoning and communication abilities of students between experimental group and control group, and 3) study the mathematical reasoning and communication abilities of student learning by using an organizing mathematics learning activities using inquiry co-operation model. The subjects were eight grade students of Kanjanapisek Witthayalai Nakornphathom School in the second semester of the academic year 2016 by purposive sampling. There were 34 students in the experimental group and 34 students in the control group. The experimental instruments constructed by the researcher were lesson plans focusing an organizing mathematics learning activities using inquiry co-operation model and conventional plans. The instruments for data collection were mathematical reasoning ability tests and mathematical communication ability tests and the instruments for data analysis were mean, standard deviation and t-test. The results of the study revealed that 1) the mathematical reasoning and communication abilities of students after learning by using an organizing mathematics learning activities using inquiry co-operation model were higher than those before the experiment at a .05 level of significance, 2) the mathematical reasoning and communication abilities of the students in the experimental group were higher than those of the students in control group at a .05 level of significance, and 3) the mathematical reasoning and communication abilities of student learning by using an organizing mathematics learning activities using inquiry co-operation model were developed in positive direction.